Minutes of the Evaluation Meeting [of the Association of Physician Assistant Programs], June 5-6, 1971 - Greenberg, Suzanne B.; Glazer, David L. (1973)
Minutes of meeting held June 5, 1973 at Emory University, Atlanta, GA to "make recommendations to the Association of Physician Assistant Programs (APAP) Executive Committee concerning PA evaluation, both in regard to evaluation to be generated by the APAP and to screen proposals to use program data by persons outside the association." Members of the committee presented ongoing research at their respective institutions resulting in the delineation of five legitimate areas of concern for evaluation: (1) felt need for PAs, (2) student selection, (3) specific training program evaluation, (4) studies of impact on delivery systems and (5) maintenance of statistical data on graduates. Each of these areas of evaluation is defined in greater detail in the minutes.